2013
DOI: 10.1515/mammalia-2011-0138
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, diet, movements, and survival of an isolated, unmanaged raccoon Procyon lotor (Procyonidae, Carnivora) population on the Outer Banks of North Carolina

Abstract: Raccoons ( Procyon lotor ) are highly adaptable meso-carnivores that inhabit many environments, including the Atlantic barrier islands, where their role as predators of declining, beach-nesting bird and turtle species is of particular interest. Population models that improve our understanding of predator-prey dynamics are receiving increasing attention in the literature; however, their effective application requires site-specific information on population parameters. We studied an unharvested raccoon populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Closed study sites like islands are rare in ecology and offer the opportunity to generate true survival and recruitment estimates from capture-recapture models by eliminating the confounding effects of immigration and emigration. Our estimated population size was higher in primary periods 1 and 3 than in primary period 2, which corresponds with the generally higher mortality of raccoons over the late winter and early spring months (Parsons et al 2012). Likewise, our model estimates of survival were lower between primary period 1 and 2 than between primary period 2 and 3 but the period 1-2 estimate is likely biased because of animals either avoiding baited traps or spending most of their time in the unsampled marshes as previously discussed.…”
Section: Biological Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Closed study sites like islands are rare in ecology and offer the opportunity to generate true survival and recruitment estimates from capture-recapture models by eliminating the confounding effects of immigration and emigration. Our estimated population size was higher in primary periods 1 and 3 than in primary period 2, which corresponds with the generally higher mortality of raccoons over the late winter and early spring months (Parsons et al 2012). Likewise, our model estimates of survival were lower between primary period 1 and 2 than between primary period 2 and 3 but the period 1-2 estimate is likely biased because of animals either avoiding baited traps or spending most of their time in the unsampled marshes as previously discussed.…”
Section: Biological Resultsmentioning
confidence: 50%
“…We derived in situ recruitment from our top model results. marsh edge and forage extensively in the marshes themselves (Parsons et al 2012). We speculate that these individuals, despite almost daily flooding due to the tidal regime, adapted to local conditions and spent most of their time in these marshes, and only rarely ventured into the uplands where cameras were located (Parsons et al 2012).…”
Section: Assumption Violationsmentioning
confidence: 84%
See 1 more Smart Citation
“…The raccoon, Procyon lotor, adapts to a wide variety of resources, therefore displaying high diversity in both diet and foraging behaviors. Raccoons are highly adaptive meso-carnivores, and are successful in many ecosystems due to their consumption of a wide variety of flora and fauna [8,9]. Barton and Roth suggested that raccoon diet choice might be influenced by multiple factors in addition to food item abundance, including dispersal patterns, raccoon density, and population age structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…It ranges throughout rural and urban areas of North America (Parsons et al, 2011). Parsons et al (2011) also noted that raccoons thrive in areas where there are human developments and the absence of large predators.…”
Section: Introductionmentioning
confidence: 99%